Oxidative stress limits growth of Chlamydomonas reinhardtii (Chlorophyta, Chlamydomonadales) exposed to copper ions at the early stage of culture growth. Issue 4 (4th July 2021) - Nowicka, Beatrycze; Zyzik, Magdalena; Kapsiak, Maja; Ogrodzińska, Wiktoria; Kruk, Jerzy
ABSTRACT: Copper is a micronutrient essential for the growth of photosynthetic organisms. However, it is highly toxic at supraoptimal concentrations, causing oxidative stress. Living organisms defend themselves against reactive oxygen species (ROS) via the synthesis of ROS-detoxifying enzymes and low-molecular-weight antioxidants. In the present paper, the antioxidant response of model green microalga Chlamydomonas reinhardtii exposed to 20 and 25 µM CuSO4 was monitored during various stages of growth (exponential growth phase, stationary phase, decline phase). The aim of the study was to measure the effect of Cu on algal growth along with antioxidant responses. The content of both hydrophilic (ascorbate and its oxidized form dehydroascorbate, total thiols, proline) and hydrophobic (tocopherols, plastoquinol, plastochromanol) low-molecular-weight antioxidants, as well as the activity of superoxide dismutase, catalase and ascorbate peroxidase were measured. After seven days of growth, a significant decrease in cell number and chlorophyll content was observed in Cu-treated culture batches. This was accompanied with the increase in total ascorbate content and antioxidant enzyme activity, whereas the levels of major prenyllipid antioxidants decreased. The differences in cell number and chlorophyll content were less pronounced at later growth stages. There were also no pronounced increases in ascorbate and antioxidant enzyme activities. It was concluded that the enhanced oxidative stress occurred at the earlier stages of growth. This conclusion is supported by the results of the assessment of lipid peroxidation markers.